Synergistic effect of essential oils and chlorhexidine against planktonic and biofilm-forming cells of Malassezia pachydermatis - Peter Váczi; Eva Čonková; Zuzana Malinovská (Veterinary and Animal Science)
Malassezia (M.) pachydermatis, is often associated with secondary infection of the skin and external auditory canal in dogs and cats. The treatment of Malassezia infections is based on the local application of antifungals often combined with antiseptics. Due to increased resistance of yeast to commonly used antimycotics, especially in biofilm-forming cells, the use of natural substances, e.g. plant essential oils, appears as a new promised option. In this study, the efficacy of selected plant essential oils (EO) – oregano, rosemary, bergamot, clove, cinnamon, and thyme – in combination with chlorhexidine on both planktonic and biofilm-forming cells of M. pachydermatis, was investigated. The checkerboard test was used to determine the effect of chlorhexidine combined with individual EOs. According to the FICI (fractional inhibitory concentration index) in planktonic cells, most combinations showed additive effect, except for thyme and rosemary EO, where a synergistic effect was found (33.3 % and 16.7 % respectively). In the biofilm-forming cells, a synergistic effect was noted in chlorhexidine combined with bergamot EO, recorded in 6 isolates (33.3 %), and with thyme and oregano EO, detected in 3 isolates (16.7 %). A significant decrease (p ˂ 0.05) was found in FIC (fractional inhibitory concentration) compared to MIC (minimum inhibitory concentration), for both planktonic and biofilm-forming cells. Based on the obtained results, we can conclude that the combination of chlorhexidine with EOs achieved better efficiency than when using each agent alone and made it possible to reduce the concentration of both, and a sufficient antifungal and antibiofilm effect was achieved in M. pachydermatis strains.